GlicoPro, Novel Standardized and Sterile Snail Mucus Extract for Multi-Modulative Ocular Formulations: New Perspective in Dry Eye Disease Management - Rita Mencucci; Giovanni Strazzabosco; Virginia Cristofori; Andrea Alogna; Daria Bortolotti; Roberta Gafà; Michela Cennamo; Eleonora Favuzza; Claudio Trapella; Valentina Gentili; Roberta Rizzo (MDPI AG, 2021)
This study aimed to evaluate the mucoadhesive and regenerative properties of a novel lubricating multimolecular ophthalmic solution (GlicoPro®) extracted from snail mucus and its potential anti-inflammatory and analgesic role in the management of dry eye disease (DED). GlicoPro bio-adhesive efficacy was assessed using a lectin-based assay, and its regenerative properties were studied in a human corneal epithelial cell line. In vitro DED was induced in human corneal tissues; the histology and mRNA expression of selected genes of inflammatory and corneal damage biomarkers were analyzed in DED tissues treated with GlicoPro. A higher percentage of bio-adhesivity was observed in corneal cells treated with GlicoPro than with sodium hyaluronate-based compounds. In the scratch test GlicoPro improved in vitro corneal wound healing. Histo-morphological analysis revealed restoration of cellular organization of the corneal epithelium, microvilli, and mucin network in DED corneal tissues treated with GlicoPro. A significant reduction in inflammatory and ocular damage biomarkers was observed. High-performance liquid chromatography-mass spectrometry analysis identified an endogenous opioid, opiorphin, in the peptide fraction of GlicoPro. In conclusion, GlicoPro induced regeneration and bio-adhesivity in corneal cells; moreover, considering its anti-inflammatory and analgesic properties, this novel ophthalmic lubricating solution may be an innovative approach for the management of DED.